2004
DOI: 10.1111/j.1440-1843.2003.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of community‐acquired pneumonia in children caused by Mycoplasma pneumoniae: Serological results of a prospective, population‐based study in primary health care

Abstract: Incidence of community-acquired pneumonia in children caused byMycoplasma pneumoniae : Serological results of a prospective, population-based study in primary health care KORPPI M, HEISKANEN-KOSMA T, KLEEMOLA M. Respirology 2004; 9 : 109-114 Objective:The objective of the present study was to assess the incidence of community-acquired pneumonia (CAP) in children caused by Mycoplasma pneumoniae . Methodology: During 12 months in 1981-1982, all CAP cases in a defined child population were registered. M. pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 34 publications
2
82
0
6
Order By: Relevance
“…Furthermore, coinfection with a pathogen in addition to M. pneumoniae is common but rarely identified via clinical testing, making it difficult to draw specific conclusions about therapeutic effects. 9,38 Finally, no study included in our analysis took into account the duration of illness before the start of antibiotic therapy. It is possible that the timing of intervention relative to the start of symptoms is related to the outcome.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, coinfection with a pathogen in addition to M. pneumoniae is common but rarely identified via clinical testing, making it difficult to draw specific conclusions about therapeutic effects. 9,38 Finally, no study included in our analysis took into account the duration of illness before the start of antibiotic therapy. It is possible that the timing of intervention relative to the start of symptoms is related to the outcome.…”
Section: Figurementioning
confidence: 99%
“…3 M. pneumoniae is a common cause of CAP and other community-acquired lower respiratory tract infections (CA-LRTIs), particularly in school-age children and adolescents, but there are large gaps in our understanding of this disease. 3,4 Prevalence estimates vary from 10% to 40% in pediatric CA-LRTI, [5][6][7][8][9] and few studies address treatment recommendations. 4,10 Additionally, the IDSA guidelines target the use of macrolides in CA-LRTI as an area needing additional research.…”
mentioning
confidence: 99%
“…Even when the diagnosis is made, there is evidence that MP infections are often mixed; Korppi et al 4 reported .50% of MP CAP to be mixed infections, with Streptococcus pneumoniae identified in two-thirds of cases. MP may precede and intensify subsequent infections with various respiratory viruses and bacteria.…”
mentioning
confidence: 99%
“…Age is an important predictor of etiologic agent in pneumonia. 11,12 13 found hospitalization rates of 67% for children younger than 4 years old, 5% for children 5 to 9 years old, and 9% for children 10 to 14 years old. The present study assessed only hospitalized children, which explains its large share of subjects younger than 5 years old.…”
Section: Discussionmentioning
confidence: 99%